PERAN BAZNAS DALAM DISTRIBUSI ZAKAT SEBAGAI UPAYA DALAM MENGENTASKAN KEMISKINAN - Galuh Nashrulloh Kartika Mayangsari Rofam; Saifullah Abdushshamad (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2019)
This research is a qualitative research using descriptive analysis. The primary data in this study were obtained from BAZNAS Kota in Banjarmasin, while the secondary data was obtained from the report on zakat collection in 2017-2018, books, scientific journals, articles and others. Data collection in this study uses interview, observation, literature study and documentation techniques. The results of this study concluded that zakat funds were distributed in the economic, education and health sectors as follows: 1) in the 2017 period zakat funds amounted to Rp 1,039,888,966, infaq funds with a nominal amount of Rp 695,288,406.20, amil funds of Rp. 113,725,141,25, and a grant of Rp. 408,785,000, -. 2) In the 2018 period, zakat funds amounted to Rp 1,521,732,046, - infaq funds with a nominal value of Rp 956,137,200, - amil funds of Rp. 164,883,624, - and a grant of Rp. 722,980,000, -. The zakat is distributed through several programs, namely Banjarmasin Peduli, Banjarmasin Sejahtera, Banjarmasin Takwa, Banjarmasin Sehat and Banjarmasin Cerdas.